Research on the Deformation Laws of Adjacent Structures Induced by the Shield Construction Parameters - Jinhua Wang; Nengzhong Lei; Xiaolin Tang; Yulin Wang (Buildings, 2025)
Taking the shield construction of Xiamen Metro Line 2 tunnel side-crossing the Tianzhushan overpass and under-crossing the Shen-Hai Expressway as the engineering background, FLAC3D 6.0 software was used to examine the deformation of adjacent structures based on shield construction parameters in upper-soft and lower-hard strata. The reliability of the numerical simulation results was verified by comparing measured and predicted deformations. The study results indicate that deformation of the pile will occur during the construction of the tunnel shield next to the pile foundation. The shape of the pile deformation curve in the horizontal direction is significantly influenced by the distance from the pile foundation to the adjacent tunnel’s centerline, as well as by soil bin pressure, grouting layer thickness, and stress release coefficient. During the tunnel shield construction beneath the expressway, increasing the soil bin pressure, the grouting layer thickness, and reducing the stress release coefficient can effectively minimize surface deformation and differential settlement on both sides of the deformation joints between the bridge and the roadbed. The practice shows that, by optimizing shield construction parameters in upper-soft and lower-hard strata, the deformation of nearby bridges and pavements can be kept within allowable limits. This is significant for reducing construction time and costs. The findings offer useful references for similar projects.